THE INFLUENCE OF CONFLICT AND STRESS ON EMPLOYEE PERFORMANCE OF PDAM EMPLOYEES IN SERVICE AREA II OF MAKASSAR CITY - Ahmad Fadli; Akhmad, Akhmad; Andi Risfan Rizaldi (International Journal of Economic Research and Financial Accounting, 2024)
This research is a quantitative descriptive study aimed at determining and analyzing the Influence of Conflict and Stress on Employee Performance at the Regional Water Company (PDAM) in Service Area II of Makassar City. The data collection methods used in this research were observation, questionnaires, and documentation. The population and sample used in this research consisted of 52 respondents, with the data analysis method being multiple linear regression analysis processed using Statistical Product and Service Solutions (SPSS) Version 27. Regarding the influence of conflict and stress on the permormance at PDAM Employess in service area II of Makassar City which was discussed in the previous chapters, the author draws the important conclusion that conflict and stress have a positive and significant on the permormance.